IDENTITY CONSTRUCTION IN SAMUEL BECKETT’S WAITING FOR GODOT - Fajar, Yusri (Balai Bahasa Jawa Timur, 2013)
This paper scrutinizes the formation of the identity of the characters in Samuel Beckett?s famous play Waiting for Godot. One of the characters whose identity is constructed is Godot, a mysterious absent figure. The other characters, such as Vladimir and Estragon actively construct Godot?s identity. Thus, the formation of identity cannot be separated from the social construction in which a lot of characteristics are attributed by the members of the large community. The theory of identity elaborated by Stuart Hall and Erikson is employed to examine the play. The study shows that Godot and other characters? identity is unstable and fluid. The characteristics of their identity are ambiguous and even challenged. Abstrak: Artikel ini mengkaji pembentukan identitas karakter dalam drama terkenal Waiting for Godot karya Samuel Beckett. Salah satu karakter yang dikonstruksi identitasnya adalah Godot, sosok misterius yang tidak pernah muncul. Karakter lain, seperti Vladimir dan Estragon secara aktif mengonstruksi identitas Godot. Oleh sebab itu, pembentukan identitas tidak dapat dipisahkan dari konstruksi sosial yang dimasuki banyak karakteristik oleh anggota masyarakat luas. Teori identitas Stuart Hall dan Erikson digunakan untuk menganalisis drama tersebut. Hasil analisis menunjukkan bahwa identitas Godot dan karakter lain tidak stabil dan cair. Karakteristik identitas mereka ambigu dan bahkan meragukan. Kata-Kata Kunci: identit; ambiguitas; Godot